Archival of government electronic information - Tan, Stephen Tiong Soon. (2009)
Today as more and more Government Departments as well as business companies ' go electronic' there is a growing use of electronic mail as a main mode of communication. These E-mail data contain approval of proposals and confirmation of decisions. The current Government filing and document management procedures do not fully recognise the use of this media and has not been able to manage these records as part of the standard Government record management program. Therefore, in the current environment, a substantial amount of information is lost or kept by individuals with no proper record management procedures. This is leading to a major record management issue with major legal and historical implications. As the value and volume of electronic information grows the problem of management of the information, the archival concerns and the legal aspect of electronic information become critical.